Peningkatkan Kesadaran Dan Pengelolaan Kesehatan Pada Orang Dewasa Melalui Edukasi Dan Pemeriksaan Kadar Kolesterol Sebagai Skrining Awal Hiperkolesterolemia - Fachruddin, Ismi Irfiyanti; Sakinah Amir; Andi Hardianti; Syamsuriah, Syamsuriah; Ulfa Dyia Atiqa (Jurnal Aksi dan Inovasi Sosial, 2025)
Overweight and obesity have emerged as significant global health issues, especially in Indonesia. This issue impacts not just physical appearance but also elevates the risk of several chronic ailments, including hypercholesterolemia, which may lead to heart disease. Routine cholesterol assessments are crucial for the early identification of hypercholesterolemia. The community service was a comprehensive cholesterol assessment accompanied by health education on hypercholesterolemia and its associated problems. The examination results indicated that 74% of people were overweight or obese, while the remainder had normal weight; moreover, 67% exhibited elevated cholesterol levels. Enhancing public knowledge of the significance of sustaining body weight within the normative range and adopting a healthy lifestyle may mitigate the incidence of metabolic illnesses in the future.